Community resilience of women in rural areas of Lempira in the Republic of Honduras - Junko Miyamoto; Minato Nakazawa (Población y Salud en Mesoamérica, 2024)
Introduction: Building community resilience is an important part of disaster preparedness. This study aims to determine the factors that influence the status of community resilience and their relationship with social capital. Methods: Data were collected between August and November 2021 by surveying a group of over 18-year-old females in the Republic of Honduras where hit by two hurricanes and a pandemic in 2020. Cluster sampling was used in this study, and face-to-face interviews were done while visiting their houses. The Conjoint Community Resiliency Assessment Measure (CCRAM) was used to examine community resilience score, while the association between social capital, basic attributes, disaster preparedness, and whether the damages by the two hurricanes in 2020, etc. For statistical analysis, we applied multiple regression analysis. Results: Bonding social capital was a factor that lowered community resilience, and bridging social capital was a factor that raised community resilience. The community resilience for those with an elementary school education was higher than those without education but not different from those with more than an elementary school education. Conclusions: Bridging social capital and completing primary education increased community resilience.